TEACHER ATTITUDE AND STUDENT-TEACHER RELATIONSHIP AS PREDICTORS OF ENGLISH AS A FOREIGN LANGUAGE (EFL) STUDENT ENGAGEMENT - Dian Nurafni Hasman; Alberth Alberth; La Ode Nggawu (Pusat Pengembangan Pendidikan dan Penelitian Indonesia (P4I), 2026)
This study investigates the predictive relationships between Students' Perceived Teacher Attitude, Student-Teacher Relationship, and Student Engagement in English as a Foreign Language (EFL) classes at SMKN 01 Bombana, Indonesia. Student engagement is considered a critical factor in language learning success, particularly in vocational school contexts where learners often show low motivation and limited perceived relevance of English for future careers. The study aims to examine how teacher-related factors contribute to student engagement both individually and jointly. A quantitative explanatory design was employed using Partial Least Squares Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The sample consisted of 193 students from Grades 10 to 12, selected through total population sampling. Data were collected using a structured questionnaire with a five-point Likert scale. The results show that both predictor variables significantly influence student engagement. Students' Perceived Teacher Attitude has a positive and significant effect on Student Engagement (β = 0.377, t = 4.962, p < 0.001), and Student-Teacher Relationship also has a positive and significant effect (β = 0.386, t = 5.697, p < 0.001). The model explains 50.5% of the variance in Student Engagement (R² = 0.505), indicating moderate explanatory power. Among the two predictors, Student-Teacher Relationship demonstrates a slightly stronger influence. The study concludes that student engagement in EFL classes is strongly shaped by both teacher attitude and relationship quality, highlighting the importance of interpersonal and affective dimensions in language learning, particularly in vocational education settings. ABSTRAK Penelitian ini mengkaji hubungan prediktif antara sikap guru yang dipersepsikan siswa, hubungan Guru-Siswa, dan keterlibatan siswa dalam kelas bahasa Inggris sebagai bahasa asing (EFL) di SMKN 01 Bombana, Indonesia. Keterlibatan siswa dipandang sebagai faktor penting dalam keberhasilan pembelajaran bahasa, terutama dalam konteks sekolah kejuruan yang sering menunjukkan motivasi rendah dan persepsi relevansi bahasa Inggris yang terbatas bagi karier siswa. Penelitian ini bertujuan menguji sejauh mana faktor-faktor terkait guru memengaruhi keterlibatan siswa, baik secara individual maupun secara bersama-sama. Desain penelitian yang digunakan adalah kuantitatif eksplanatori dengan analisis Partial Least Squares Structural Equation Modeling (PLS-SEM) melalui perangkat lunak SmartPLS. Sampel penelitian berjumlah 193 siswa kelas 10 hingga 12 yang dipilih melalui teknik total population sampling. Data dikumpulkan menggunakan kuesioner terstruktur dengan skala Likert lima poin. Hasil penelitian menunjukkan bahwa kedua variabel prediktor berpengaruh positif dan signifikan terhadap keterlibatan siswa. Sikap guru yang dipersepsikan siswa berpengaruh positif dan signifikan (β = 0,377, t = 4,962, p < 0,001), demikian pula hubungan Guru-Siswa (β = 0,386, t = 5,697, p < 0,001). Model penelitian menjelaskan 50,5% varians Keterlibatan Siswa (R² = 0,505), yang menunjukkan kekuatan penjelas model yang moderat. Di antara kedua prediktor, hubungan Guru-Siswa menunjukkan pengaruh yang sedikit lebih kuat. Penelitian ini menyimpulkan bahwa keterlibatan siswa dalam kelas EFL sangat dipengaruhi oleh sikap guru maupun kualitas hubungan guru-siswa, sehingga menegaskan pentingnya dimensi interpersonal dan afektif dalam pembelajaran bahasa, khususnya pada konteks pendidikan kejuruan.